DM1: autoetnografía de un cuerpo en disputa - Arce Coronel, Xiomi Camila (Pontificia Universidad Católica del Perú, 2025)
This chronic explores the experience of living with a chronic disease, type 1 diabetes mellitus (DM1), from an autoethnographic perspective, highlighting the tensions between Western biomedicine and traditional and alternative therapies in a hybrid cultural context. Through a narrative that encompasses diagnosis, treatment, and cultural implications, it reflects on how the disease becomes a frontier between different systems of knowledge and power. In addition, the impact of these experiences on identity, the body, and conceptions of health are analyzed, addressing illness not only as a physiological phenomenon, but also as a cultural, symbolic, and political phenomenon. In this process, writing becomes a tool to understand and resignify vulnerability and the relationship with the body.

La presente crónica explora la experiencia de vivir con una enfermedad crónica, la diabetes mellitus tipo 1 (DM1), desde una perspectiva auto etnográfica, destacando las tensiones entre la biomedicina occidental y las terapias tradicionales y alternativas en un contexto cultural híbrido. A través de una narrativa que abarca el diagnóstico, el tratamiento, y las implicancias culturales, se reflexiona sobre cómo la enfermedad se convierte en una frontera entre diferentes sistemas de conocimiento y poder. Además, se analiza el impacto de estas experiencias en la identidad, el cuerpo y las concepciones de la salud, abordando la enfermedad no solo como un fenómeno fisiológico, sino también como un fenómeno cultural, simbólico y político. La escritura, en este proceso, se convierte en una herramienta para comprender y resignificar la vulnerabilidad y la relación con el cuerpo.
DM1: Autoethnography of a body in dispute
Keywords: Disease; Autoethnography; Type 1 diabetes; Body; Biomedicine; Enfermedad; Autoetnografía; Diabetes tipo 1; Cuerpo; Biomedicina; https://purl.org/pe-repo/ocde/ford#5.04.03